Las Cuevas Bay, Trinidad - (:unkn) unknown (Print Master Limited, Marabella, Trinidad, 2009)
Another popular beach on Trinidad's north coast is Las Cuevas which is approximately eight (8) km east of Maracas Bay. The name "Las Cuevas" is derived from the Spanish word for caves and there are many caves on this beach. The bay is more sheltered then Maracas and is therefore calmer which provides for excellent swimming conditions.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Las Cuevas; Beaches--Trinidad and Tobago; Coasts--Trinidad and Tobago; Coconut palm--Trinidad and Tobago